2015
DOI: 10.7448/ias.18.1.20019
|View full text |Cite
|
Sign up to set email alerts
|

The clock is ticking: the rate and timeliness of antiretroviral therapy initiation from the time of treatment eligibility in Kenya

Abstract: IntroductionUnderstanding the determinants of timely antiretroviral therapy (ART) initiation is useful for HIV programmes intent on developing models of care that reduce delays in treatment initiation while maintaining a high quality of care. We analysed patient- and facility-level determinants of time to ART initiation among patients who initiated ART in Kenya.MethodsWe collected facility-level information and conducted a retrospective chart review of adults initiating ART between 2007 and 2012 at 51 health f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…However little variation was seen in ART initiation among patients by CD4 level or WHO staging. Similar results were seen in studies conducted in Kenya and Rwanda which found little or no variation in ART initiation WHO staging, however these studies saw variation by CD4 count category [21, 22]. It appears that prioritization for treatment initiation among HIV-positive persons is not currently occurring at a significantly different rate based on CD4 level within the selected facilities we studied in South Africa.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However little variation was seen in ART initiation among patients by CD4 level or WHO staging. Similar results were seen in studies conducted in Kenya and Rwanda which found little or no variation in ART initiation WHO staging, however these studies saw variation by CD4 count category [21, 22]. It appears that prioritization for treatment initiation among HIV-positive persons is not currently occurring at a significantly different rate based on CD4 level within the selected facilities we studied in South Africa.…”
Section: Discussionsupporting
confidence: 84%
“…While not affecting timeliness of ART initiation, age influenced rate of ART initiation with adolescents initiating at a faster rate than adults of all ages. Similar studies in sub-Saharan Africa saw no variation in timeliness of ART initiation by age [21, 22]. While the present analysis is limited in scope to explain the differences in timeliness by age, this is likely partially explained by the high proportion of pregnant women falling in the 15–24 age category.…”
Section: Discussionsupporting
confidence: 42%
“…The relationship was approximately linear, precisely estimated and robust to adjustment for age, sex and other baseline covariates. This is some of the first quantitative evidence on the association between CD4 count at presentation and ART uptake , confirming evidence in qualitative studies .…”
Section: Discussionsupporting
confidence: 79%
“…Table 2 presents hazard ratios of ART initiation associated with each predictor in the full sample. The hazard of ART initiation fell by 17% (95% CI 14,20) for every 100-cell increase in baseline CD4 count, with CD4 count modelled continuously. These effects were robust to alternate specifications controlling for age, sex, age-sex interactions, year of first recorded CD4 count and clinic fixed effects.…”
Section: Resultsmentioning
confidence: 99%
“…Despite increasing access to antiretroviral therapy (ART), the proportion of eligible patients initiated on treatment remains suboptimal [1,2]. The 90-90-90 targets aim for 90% of people living with HIV (PLHIV) to know their HIV status, 90% of PLHIV to be on ART, and 90% of patients on ART to attain virological suppression by 2020 [3].…”
Section: Introductionmentioning
confidence: 99%